Observations by Mr. Sandford Fleming on the general land policy of the Hudson's Bay Company [electronic resource]. - Fleming, Sandford, Sir, 1827-1915 ([London? : s.n.], 1882)
Cover title. At head of title: Confidential. Electronic reproduction. Mode of access: Internet. 44